Patients' expectation and satisfaction with removable dental prosthesis therapy and correlation with patients' evaluation of the dentists - De Siqueira, Graziele Pereira; Dos Santos, Mateus Bertolini Fernandes; Dos Santos, Jarbas Francisco Fernandes; Marchini, Leonardo [UNESP] (MJS Publishing, Medical Journals Sweden AB, 2013)
Objective. Considering that patients' satisfaction is one of the most important goals in conducting removable dental prosthesis (RDP) therapy and the fact that there are many factors which influence this parameter, the present study aims to evaluate the expectation before and satisfaction after therapy with RDP in patients who seek such therapy. As a secondary objective, other variables that may be associated with patient satisfaction are also evaluated, such as gender, age, Kennedy's classification of the arch supporting the RDP, the number of RDP adjustments after delivery and patients' evaluation of the dentists' conduct. Materials and methods. A sample of 44 patients who received RDP therapy were assigned visual analog scale scores for their expectation before and satisfaction after therapy regarding chewing, aesthetics, comfort and phonetics. They also completed a questionnaire concerning the dentists' conduct. Results. There was no statistically significant difference among scores concerning different genders, age, number of post-delivery settings and arch involved in the RDP. Regarding patients' evaluation of the dentists' conduct, there was a predominance of positive evaluations, but only different answers to the statement (i.e. 'The dentist I saw thoroughly explained the recommended treatment before it commenced') present statistically significant different scores for chewing (p = 0.040) and phonetics (p = 0.046). Conclusions. The average visual analog scale scores were high for both expectation prior to treatment and satisfaction after treatment; however, the scores for expectations were higher than those for satisfaction. © 2013 Informa Healthcare.
Keywords: Patient expectations; Patient satisfaction; Removable dental prosthesis; adult; age; aged; dental procedure; doctor patient relation; edentulousness; female; histology; human; male; mastication; middle aged; nonparametric test; patient satisfaction; phonetics; psychological aspect; questionnaire; removable partial denture; sex difference; tooth arch; Adult; Age Factors; Aged; Dental Arch; Dentist-Patient Relations; Denture, Partial, Removable; Esthetics, Dental; Female; Humans; Jaw, Edentulous, Partially; Male; Mastication; Middle Aged; Patient Satisfaction; Phonetics; Questionnaires; Sex Factors; Statistics, Nonparametric